Biodiversity assessment of freshwater shrimps and crabs in Nee Soon swamp area, Singapore. - Sun, Samantha Wenyu. (2011)
The Nee Soon Swamp Forest is one of the most important and the last vestige of swamp forests in Singapore. To date, most studies have placed its emphasis on taxonomic studies without any detailed recordings of the distribution and population characteristics of freshwater shrimps and crabs in the Nee Soon Swamp area. As such, with the two methods, hand sampling and the trap sampling, complementing each other, the first set of baseline data of freshwater decapods residing in the Nee Soon freshwater swamp was obtained. After conducting four months of survey, the Shannon-Weiner index had show that the middle reach of the Nee Soon freshwater swamp showed greater species diversity in general. Numerical dominance was observed in the population densities of both M.malayanum (1 - 32.5 individuals per site) and C.malayensis (9.25 - 29.75 individuals per site). In contrast, M.sundaicum and M.platycheles were found in much lower numbers, with mean abundance at all sites ranging from1.13-2.13 and 0.88-1.75 individual per site respectively by hand sampling. Trap sampling on the other hand yielded different results, with Mainpond2 having the highest mean abundance of M.sundaicum (13.25±6.48 individuals per site) and M.platycheles having highest abundance in Midpoint2 (13.25±11.18 individuals per site). New findings were observed at USR1 where M.nipponense and P.amnicus were observed to reside at the edge of Nee Soon freshwater swamp for the first time. Significant results were also recorded for the endemic species P.reticulata, with Midpoint 1 bearing the highest population density of 7 ± 3.8 crabs per site, and mean carapace length of 4.213 ± 0.27 cm. Results obtained are to facilitate future conservation efforts in this area. The future of conservation management proves to be a promising one.